The Employment Cluster of Omnibus Law: Embodiment the Concept of Nachtwakerstaat or Welfarestate? - Anak Agung Gede Duwira Hadi Santosa; Kadek Agus Sudiarawan; I Made Marta Wijaya (Universitas Lampung, 2021)
The presence of the omnibus law of the Employment Cluster of Job Creation Law haven’t consider to solve the crucial problems in the Manpower Law, but its further away from the purpose of the welfarestate concept and leads to the purpose of the nachtwakerstaat. The aims of this research to determine position omnibus law of the Job Creation Law after it’s passed within in the scope of welfarestate concept or nachtwakerstaat concept and to analyse the construction of labour law concept in accordance to concept of welfarestate in the future. This research used a normative legal research method with a statute approach and elaborated with a legal concept analysis approach. The results show there are crucial problems in the Employment Cluster of the Job Creation Law such as the elimination of several principal provisions in Manpower Law that indicates the role and presence of the state in labour law is getting minimum and also the Job Creation Law point out many things that returned the agreement mechanism by the parties. This show that, Employment Cluster of the Job Creation Law tends to the nachtwakerstaat concept and far away from welfarestaat concept. The solutions of the issues by doingrevision to the Employment Chapter of the Job Creation Law by adjusted the welfarestate concept, alsorestore and strengthen the function of the government as a part of industrial relations as a regulator and supervisor